Peran Dosen Dalam Memanfaatkan Media Sosial Sebagai Sarana Literasi Pembelajaran Mahasiswa - Yanuarti, Eka; Sari, Devi Purnama (JOEAI (Journal of Education and Instruction), 2019)
The purpose of this study was to determine the role of lecturers in utilizing social media as a means of learning literacy for students of IAI Curup Study Program. Research methods, descriptive qualitative. Data obtained by interview, observation and documentation analysis. Test the validity of the data using triangulation techniques. The results of the study found four themes in the role of lecturers in utilizing social media as a means of literacy namely; first, instructing students to look for current phenomena that are being updated in various social media to be analyzed and related to the learning material being studied. Second, instructing students to see various forms of daily behavior expressed through stories and writings that are updated on various social media to be analyzed and linked to the learning material being studied. Third, instructing students to share learning materials and products on various social media that they have. Fourth, inviting students to be able to analyze the news that is spread in various social media that is used as a reference for learning by accessing other sources as a reinforcement or comparison of information on social media so as to avoid Hoax news. Conclusion, the role of lecturers in the use of social media is done by; lecturers as instructors, lecturers as role models, as disseminators of knowledge and as servants of education. In the current era of information technology and social media development. Lecturers have a strategic role in efforts to use social media as a means of learning literacy for students Keywords:, Social Media, Learning Literacy